Harvesting of Non-timber Forest Products by the Local Communities in Mount Halimun-Salak National Park, West Java, Indonesia - Yelin Adalina; Dodik Ridho Nurrochmat; Dudung Darusman; Leti Sundawati (Jurnal Manajemen Hutan Tropika, 2014)
Local communities around the forest need to be involved in securing the sustainability of Mount Halimun Salak National Park (MHSNP), for example through the utilization of non-timber forest products (NTFPs) such as flora in the utilization zone. This research was aimed to provide data and information about 3 kinds of vegetation producing resin (Pinus merkusii, Agathis dammara, and Hevea brasiliensis) and the harvesting NTFPs by the community in the forest vicinity. The research was conducted in MHSNP, and data were analyzed through quantitative-descriptive. The survey method was employed in the study through interviews of respondents using structured questionnaires.   This study revealed that the vegetations at the stage of tree comprised of the following: (1) Agathis dammara (damar) with Importance Value Index (IVI) of 276.15% and density of 452 trees ha-1, (2) Pinus merkusii (pine) trees with IVI of 300.0% and density of 552 trees ha-1, and (3) Hevea brasiliensis (rubber) trees with IVI of 217.42%  and density of 85 trees ha-1. Pine, damar, and rubber sap tapping afforded contribution in 59.18, 4.41, and 60.71%, respectively of the total household incomes. Community involvement in the collection of NTFPs in national parks implicated to the increasing of the forest communities revenue and the forests will be maintained since public can get benefits from forest resources. Forest management should be directed as a producer of NTFPs that can increase the economic income of forest communities with attention to ecological factors.